2022
DOI: 10.3390/forecast4030033
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Ecological Forecasting into Undergraduate Ecology Curricula with an R Shiny Application-Based Teaching Module

Abstract: Ecological forecasting is an emerging approach to estimate the future state of an ecological system with uncertainty, allowing society to better manage ecosystem services. Ecological forecasting is a core mission of the U.S. National Ecological Observatory Network (NEON) and several federal agencies, yet, to date, forecasting training has focused on graduate students, representing a gap in undergraduate ecology curricula. In response, we developed a teaching module for the Macrosystems EDDIE (Environmental Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Teaching ecological modeling in undergraduate classrooms improves students' system thinking skills and quantitative literacy (Carey et al 2020). Similarly, we have found that integrating ecological forecasting into classrooms expands students' understanding of complex ecological concepts (Moore et al 2022). Challenge submissions are an ideal project for students in undergraduate and graduate courses and workshops, as we have discovered by training students in several university courses how to submit forecasts in collaborative teams .…”
Section: Main Textmentioning
confidence: 90%
“…Teaching ecological modeling in undergraduate classrooms improves students' system thinking skills and quantitative literacy (Carey et al 2020). Similarly, we have found that integrating ecological forecasting into classrooms expands students' understanding of complex ecological concepts (Moore et al 2022). Challenge submissions are an ideal project for students in undergraduate and graduate courses and workshops, as we have discovered by training students in several university courses how to submit forecasts in collaborative teams .…”
Section: Main Textmentioning
confidence: 90%
“…To help train new forecasters, forecasting communities of practice should help create and facilitate sharing of resources, such as teaching modules focused on fundamental forecasting concepts (Moore et al, 2022), curated lists of freely available forecasting educational resources (Willson, 2022), and community-based development of software (Boettiger et al, 2015). In addition, education in freshwater quality forecasting would be enhanced by introducing forecasting (and uncertainty) at earlier educational stages (e.g., in K-12 education; Rosenberg et al, 2022) and development of formal curricula in freshwater forecasting specifically (Moore et al, 2022).…”
Section: Further Development Of Educational Resources and Communities...mentioning
confidence: 99%
“…Ultimately, generating accurate freshwater quality forecasts requires extensive training of the forecasting team. Obtaining training in a multidisciplinary, emerging field like ecological forecasting can be challenging (Woelmer et al, 2021), motivating the need for broad sharing of educational materials (Moore et al, 2022;Willson, 2022) and opensource tools and software (e.g., Boettiger et al, 2015;Daneshmand et al, 2021;Hipsey et al, 2019;Moore et al, 2021) within active communities of practice (Figure 2: educational resources; communities of practice). Communities of practice may occur within government agencies, originate from a specific project such as the Hydrological Ensemble Prediction EXperiment (HEPEX; Schaake et al, 2007), take the form of grassroots networks such as the Ecological Forecasting Initiative (EFI; Dietze & Lynch, 2019), exist as formal professional societies, or be housed at academic institutions.…”
Section: Further Development Of Educational Resources and Communities...mentioning
confidence: 99%
“…Ultimately, generating accurate freshwater quality forecasts requires extensive training of the forecasting team. Obtaining training in a multi-disciplinary, emerging field like ecological forecasting can be challenging (Woelmer et al, 2021), motivating the need for broad sharing of educational materials (Moore et al, 2022;Willson, 2022) and open-source tools and software (e.g., Boettiger et al, 2015;Daneshmand et al, 2021;Hipsey et al, 2019;Moore et al, 2021) within active communities of practice (Fig. 2: educational resources; communities of practice).…”
Section: Further Development Of Educational Resources and Communities...mentioning
confidence: 99%
“…To help train new forecasters, forecasting communities of practice should help create and facilitate sharing of resources, such as teaching modules focused on fundamental forecasting concepts (Moore et al, 2022), curated lists of freely available forecasting educational resources (Willson, 2022), and community-based development of software (Boettiger et al, 2015). In addition, education in freshwater quality forecasting would be enhanced by introducing forecasting (and uncertainty) at earlier educational stages (e.g., in K-12 education; Rosenberg et al, 2022) and development of formal curricula in freshwater forecasting specifically .…”
Section: Further Development Of Educational Resources and Communities...mentioning
confidence: 99%